1988
DOI: 10.1016/s0886-3350(88)80088-9
|View full text |Cite
|
Sign up to set email alerts
|

A new technique of congenital cataract surgery with primary posterior chamber intraocular lens implantation

Abstract: We present a series of nine cases involving primary intraocular lens implantation in congenital cataracts. Because of the problems encountered with the technique used in the earlier cases, we developed a new surgical technique that may be described as primary epilenticular posterior chamber lens implantation followed by pars plana endocapsular lensectomy. This new technique ensures a clear pupillary area, minimizes postoperative complications, and ultimately prevents amblyopia, resulting in useful vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…The lens can be approached through the limbus or the pars plana (Goldberg & Peymann 1983; Tablante et al 1988). Using the limbal approach, a high‐viscosity ocular viscosurgical device (OVD) is preferable because the anterior chamber is often shallow and high vitreous pressure is present.…”
Section: Surgical Technique In Childrenmentioning
confidence: 99%
“…The lens can be approached through the limbus or the pars plana (Goldberg & Peymann 1983; Tablante et al 1988). Using the limbal approach, a high‐viscosity ocular viscosurgical device (OVD) is preferable because the anterior chamber is often shallow and high vitreous pressure is present.…”
Section: Surgical Technique In Childrenmentioning
confidence: 99%
“…39,40 Using the limbal approach, a highviscosity ophthalmic viscosurgical device (OVD) is preferable since the anterior chamber is often shallow and has a high vitreous pressure. If the pupil is small, which is common in eyes with congenital cataract, flexible iris retractors can be helpful; 4 are placed in the pupil before the continuous anterior capsulorhexis is performed.…”
Section: Surgical Technique In Childrenmentioning
confidence: 99%
“…Some researchers suggested anterior vitrectomy as a routine for primary capsulotomy (Tablante et al. ; Mackool ). Meanwhile, some other researchers, like Vasavada A (Vasavada & Desai ), suggested that anterior vitrectomy should be done along with primary PCCC for congenital cataract children younger than 5 years old because age was a very important issue.…”
Section: Introductionmentioning
confidence: 99%